Study on three-point bending mechanics and acoustic emission characteristics of impure salt rocks. Issue 5 (September 2019) - Liao, Yilin; Liu, Jianfeng; Li, Zhicheng; Zhang, Qiangxing; Xu, Deng; Zhu, Anqi
Abstract: In order to study the mechanics and deformation characteristics of salt rock under bending conditions, two groups salt rocks with different impurity content were subjected to three-point bending cycle loading and unloading test and simultaneous monitoring of acoustic emission based on MTS815 Flex Test GT rock mechanics test system and acoustic emission (AE) three-dimensional positioning real-time monitoring system. The research shows that: (1) The average tensile strength of pure salt rock bending tensile is 0.88MPa, and the impure salt rock is 1.72 times of pure salt rock. The impure salt rock has better resistance to crack propagation, and COMDmax and LPDmax are 82.31% and 83.47% of the pure salt rock, respectively. (2) The bending deformation failure of salt rock can be divided into four stages of linear elastic phase, nonlinear phase, post-peak crack stability expansion stage and residual phase. (3) The three-point bending deformation of salt rock is active except for the elastic phase of the line. In general, the three-point bending deformation of the polyhalite salt rock is more active. (4) Impurities weaken the plastic deformation ability of salt rock and increase the degree of brittleness.